Impact of the Free Learning Semester (FLS) on Private-Tutoring Investment - Yoonsoo Park (Korea Development Institute (KDI), 2018)
- Analysis on the impact of the Free Learning Semester (FLS) on the private-tutoring investment for middle school students revealed a significant increase among high-income households. - This study used data on 178,213 middle school students drawn from Statistics Korea's 2009-2016 Private Tutoring Expenditure Survey. - No meaningful impact was observed overall but high-income households (over 6 million won monthly) exhibited yearly increases of 15.2%p and 1.79 million won in the participation in and expenditure on private tutoring. - Such increases are due to high-income households' easy access to private tutoring and high demand in terms of tutoring for admissions and advance learning. - The FLS reduces the hours spent on academic courses. Therefore, it is easier for students from higher-income households to substitute the loss with private tutoring. - Also, the FLS alleviates students' burden of managing their grade point average (GPA), which could increase the demand for private tutoring for admissions and/or advance learning. This is particularly true among higher-income households. - The above results indicate that the FLS1em1ptdesigned to help students explore future career paths and facilitate the development of non-cognitive skills1em1ptcould widen the education gap between income groups through private tutoring. - Better quality programs are needed to supplement the cutback in academic courses in order to ease parental concerns. At the same time, more after-school programs should be introduced to assure students who have little access to private tutoring with ample educational opportunities. - Relevant polices must be designed bearing in mind that if they are not aligned with parents' needs, the biggest casualties will be low-income students who are unable to afford private tutoring.
Keywords: 330